PEMBANGUNAN JALAN LINGKAR PADANG PARIAMAN DAN PENGARUHNYA TERHADAP PERMASALAHAN KONFLIK PERTANAHAN - Afrida Afrida; Afrida Afrida (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
This article explain that some problems in societies between individu and groups, groups and groups, and groups and government actors when related white development in rural societies. It is difficult to solve the problem of land because the land owned by groups. The imfact of this condition tend to born of agrarian conflict in societies.